A Novel Hybrid Metaheuristic MPA-PSO to Optimize the Properties of Viscous Dampers - Elmira Shemshaki; Mohammad Hasan Haddad; Mohammadreza Mashayekhi; Seyyed Meisam Aghajanzadeh; Ali Majdi; Ehsan Noroozinejad Farsangi (Buildings)
Nowadays, it is very important to reduce structural vibrations and control seismic reactions against earthquakes. Nonlinear viscous dampers are known as one of the effective tools for absorbing and dissipating earthquake energy to reduce structural responses. The characteristics of nonlinear viscous dampers, including the damping coefficient, axial stiffness, and velocity exponent, play a crucial role in their performance. In this research, the optimization of nonlinear viscous damper characteristics to minimize the peak absolute displacement of the roof in three- and five-story reinforced concrete flexural frames under the El Centro earthquake record has been investigated. Structural modeling and dynamic analyses are performed using OpenSees 3.5.0 software, and damper parameter optimization is performed through a new combination of two marine predator algorithms (MPA) and particle swarm optimization (PSO). Furthermore, the performance of the new algorithm is compared with each of these methods separately to evaluate the efficiency improvement for displacement reduction. The results show that the hybrid algorithm has demonstrated significant performance improvement compared to the independent methods in identifying optimal values. Specifically, in the three-story frame, the roof displacement using the MPA-PSO method was 0.77026, which is lower than 0.77140 with the PSO method. Additionally, the damping coefficient in this method decreased to 14.22824 kN·s/mm, which is a significant reduction compared to 19.32417 kN·s/mm in the PSO method. Furthermore, in the more complex five-story frame, the two comparison methods were unable to reach the optimal solution, while the proposed method successfully found an optimal solution. These results validate the performance and advantages of the proposed hybrid algorithm.